2023
DOI: 10.31031/psprj.2023.04.000594
|View full text |Cite
|
Sign up to set email alerts
|

From a Sustainability Perspective, Why Should Bioplastics Be Used for Additive Manufacturing?

Abstract: As climate change awareness increases, the worldwide interest in efficiently using resources, materials, and energy increases. From producers to consumers, the demand for sustainability-oriented processes has become stronger across all stock market sectors. Additive Manufacturing (AM) is a promising and relatively new manufacturing process that helps to overcome supply chain, logistics, and environmental issues that traditional processes face. Fortunately, AM can process different raw materials, such as glass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…In 2023, the Tissue Pack Innovation Lab identified that 92% and 86% of packaging was made from plastic, with 77% and 75% being recyclable for kitchen towels and toilet paper, respectively [102]. Regarding the biodegradability of this type of packaging, it all depends on the type of plastic used [113]. Thus, hygiene tissue companies are exploring the use of renewable and biodegradable materials to achieve more sustainable packaging for their products [25].…”
Section: After-use Disposal Implicationsmentioning
confidence: 99%
“…In 2023, the Tissue Pack Innovation Lab identified that 92% and 86% of packaging was made from plastic, with 77% and 75% being recyclable for kitchen towels and toilet paper, respectively [102]. Regarding the biodegradability of this type of packaging, it all depends on the type of plastic used [113]. Thus, hygiene tissue companies are exploring the use of renewable and biodegradable materials to achieve more sustainable packaging for their products [25].…”
Section: After-use Disposal Implicationsmentioning
confidence: 99%